2014
DOI: 10.1038/jid.2013.394
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal CCL27 Expression Is Regulated during Skin Development and Keratinocyte Differentiation

Abstract: RNA aptamer provides a novel approach for the induction of apoptosis by targeting the HPV16 E7 oncoprotein. PLoS One 8: e64781 Reyes-Reyes EM, Teng Y, Bates PJ (2010) A new paradigm for aptamer therapeutic AS1411 action: uptake by macropinocytosis and its stimulation by a nucleolin-dependent mechanism. Cancer Res 70:8617-29 Wittmann M, Doble R, Bachmann M et al. (2012) IL-27 regulates IL-18 binding protein in skin resident cells. PLoS One 7: e38751 Zhou J, Bobbin ML, Burnett JC et al. (2012) Current progress o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
8
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 14 publications
4
8
0
1
Order By: Relevance
“…Whether the enhanced CCL27 signal we identified in the inner foreskin is responsible for an influx or induction of CCR10-expressing HIV target cells warrants further investigation. Our experiments of adding exogenous CCL27 to inner foreskin tissue cultures did reveal that this chemokine induced the movement of tissue-resident CD3+CD4+ T cells to the epithelium of the inner foreskin and may be compatible with in vitro monolayer and organotypic skin cultures showing that CCL27, expressed by epidermal keratinocytes 33 , enhanced the influx of CCR10+CD4+ T cells into inflamed skin. Our CCL27 data also appear to be reminiscent of studies that have investigated wound healing 33,34 , where it has been shown that upon burn-wound injury, CCL27 produced by keratinocytes promotes tissue repair.…”
Section: Discussionsupporting
confidence: 65%
“…Whether the enhanced CCL27 signal we identified in the inner foreskin is responsible for an influx or induction of CCR10-expressing HIV target cells warrants further investigation. Our experiments of adding exogenous CCL27 to inner foreskin tissue cultures did reveal that this chemokine induced the movement of tissue-resident CD3+CD4+ T cells to the epithelium of the inner foreskin and may be compatible with in vitro monolayer and organotypic skin cultures showing that CCL27, expressed by epidermal keratinocytes 33 , enhanced the influx of CCR10+CD4+ T cells into inflamed skin. Our CCL27 data also appear to be reminiscent of studies that have investigated wound healing 33,34 , where it has been shown that upon burn-wound injury, CCL27 produced by keratinocytes promotes tissue repair.…”
Section: Discussionsupporting
confidence: 65%
“…The levels of IL‐6, IL‐8, and IL‐10 were measured but were all below detection levels in adult and fetal skin (lower limit detection levels were 0.88 pg/mg, 0.63 pg/mg, and 1.63 pg/mg, respectively). Further, the main T‐cell chemoattractants during skin homeostasis are CCL17 and CCL27 . Fetal skin contained significant lower levels of both CCL17 and CCL27 (Figure B, C).…”
Section: Resultsmentioning
confidence: 95%
“…Besides, IL17 is supposed to downregulate CCL27 expression [22], and also further cytokines overexpressed in psoriasis, such as INF-g and TNF-a, have a pivotal role in downregulating CCL27 expression at later stages of psoriatic plaques [23]. Interestingly, only differentiated keratinocytes -which are known to be rather amiss in psoriasis -have been shown to strongly release CCL27 [24].…”
mentioning
confidence: 99%